2012
DOI: 10.1038/nchembio.797
|View full text |Cite
|
Sign up to set email alerts
|

Increasing O-GlcNAc slows neurodegeneration and stabilizes tau against aggregation

Abstract: Oligomerization of tau is a key process contributing to the progressive death of neurons in Alzheimer's disease. Tau is modified by O-linked N-acetylglucosamine (O-GlcNAc), and O-GlcNAc can influence tau phosphorylation in certain cases. We therefore speculated that increasing tau O-GlcNAc could be a strategy to hinder pathological tau-induced neurodegeneration. Here we found that treatment of hemizygous JNPL3 tau transgenic mice with an O-GlcNAcase inhibitor increased tau O-GlcNAc, hindered formation of tau a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
556
4
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 514 publications
(581 citation statements)
references
References 48 publications
18
556
4
3
Order By: Relevance
“…Although the mechanisms underlying the above observations remain unclear, it may be explained in part by the observations of Lim and Chang who demonstrated that increased levels of O-GlcNAc are associated with a more soluble pool of Sp1 during thermal stress (Lim and Chang 2006). This may represent altered localization of Sp1, or that Sp1 exhibits increased thermal stability when it is O-GlcNAc-modified (Lim and Chang 2006) similar to Tau (Yuzwa et al 2012). Together, the data discussed above suggest that O-GlcNAc can regulate the expression of HSPs by regulating both HSF-1 and Sp1.…”
Section: Heat Shock Protein Expressionmentioning
confidence: 94%
See 3 more Smart Citations
“…Although the mechanisms underlying the above observations remain unclear, it may be explained in part by the observations of Lim and Chang who demonstrated that increased levels of O-GlcNAc are associated with a more soluble pool of Sp1 during thermal stress (Lim and Chang 2006). This may represent altered localization of Sp1, or that Sp1 exhibits increased thermal stability when it is O-GlcNAc-modified (Lim and Chang 2006) similar to Tau (Yuzwa et al 2012). Together, the data discussed above suggest that O-GlcNAc can regulate the expression of HSPs by regulating both HSF-1 and Sp1.…”
Section: Heat Shock Protein Expressionmentioning
confidence: 94%
“…Recent data have demonstrated that inhibition of O-GlcNAcase, which leads to an increase in OGlcNAc levels, in a murine model of AD led to increased OGlcNAcylation of tau, decreased tau aggregation, and diminished neuronal cell death. Together, these data highlight the protective role of O-GlcNAc and suggest that OGlcNAcase could be a therapeutic target for slowing AD progression (Yuzwa et al 2012). Interestingly, low glucose uptake and metabolism during aging has been postulated to lead to decreased O-GlcNAcylation of key proteins such as Tau, potentially exacerbating the AD phenotype during aging (Yuzwa et al 2012).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…They postulated that tau pathology and neurodegeneration can be caused by impaired brain glucose metabolism via the down-regulation of tau O-GlcNAcylation in AD. Furthermore, O-GlcNAcylation may also inhibit tau oligomerization directly [72] . Therefore, decreased O-GlcNAcylation may promote tau-mediated neurodegeneration by promoting tau oligomerization directly and also indirectly by inducing its abnormal hyperphosphorylation [73] .…”
mentioning
confidence: 99%